The Wiley Blackwell Encyclopedia of Social and Political Movements - Snow, David A.; Della Porta, Donatella, 1956-; McAdam, Doug (Hoboken, NJ : John Wiley & Sons, 2023)
"This comprehensive, authoritative, and interdisciplinary work provides an essential reference for this growing and increasingly important area of study. Published simultaneously in print and online, the second edition of The Wiley Blackwell Encyclopedia of Social and Political Movements contains over 550 entries, exploring social and political movements and related collective phenomena throughout the world. The encyclopedia brings together a prestigious team of editors and contributors drawn from ten countries across five disciplines. including sociology, political science, anthropology, human geography, and social psychology. It is being significantly expanded and brought right up to date, following on from the first edition a decade earlier. The second edition covers a broad range of historical and modern topics reflecting significant social and political changes -- from the French revolution, to the Chinese Communist Revolution, the global women's movement, to the Arab Spring -- and from the American civil rights movement to contemporary environmentalism, the rise of nationalism, and the "me too" movement against sexual harassment. As the result of a major international collaboration, the entries in this definitive reference are organized, authored and edited by leading scholars, all of whom come to the project with exemplary track records and global standing. The encyclopedia will be available online or as a four-volume print set, structured in a user-friendly A-Z format"--
Revised edition of The Wiley-Blackwell encyclopedia of social and political movements, 2013.
Includes index.
Keywords: Social movements -- Encyclopedias; Social movements -- Political aspects -- Encyclopedias; Political participation -- Encyclopedias; Political activists -- Encyclopedias